Decreasing the Effects of Cumulative Head Injuries in Adolescent Football Players. Issue 3 (May 2023) - Beal, Judy A.
Abstract : Recent evidence indicates that there is a significant risk of short-term and long-term head injuries among high school football players. Our pediatric nursing expert, Dr. Beal, summarizes the evidence and suggests how nurses can advocate for safer adolescent football practices.